A Scientific Approach Using Peer Tutor Learning Models Can Improve Learning Outcomes Of Rounders Game - Melati, Eka Puput; Burhanuddin, Sudirman; Syahruddin, Syahruddin (UNIVERSITAS NEGERI MAKASSAR, 2021)
This research is classroom action research. The series of cycles 1 and 2 used are: 1) planning, 2) action, 3) observation, 4) reflection. The subjects of this study were fifth graders of Elementary School 156 Wonosari, Sukamaju Region of North Luwu totaled 17 students. Research data were taken through written tests and practical tests. Test data collection tools used in the form of observation guidelines, journals, questionnaires, and photo documentation. Data were analyzed quantitatively. Based on the data analysis that had been carried out, the conclusions obtained are: 1) in the first cycle has not reached the predetermined success indicators, which 75% of students get a score of 70 or more. The percentage of completeness obtained in cycle 1 is 29.41% or 5 people who completed from 17 students. Thus the research was continued to the next cycle. 2) At the second cycle meeting, the results were 94.12% or 16 students who scored > 70 out of 17 students overall. The indicators of research success which is set in this study have been achieved. Based on the results of this study, it can be concluded that the improvement of student learning outcomes for fifth graders of Elementary School 156 Wonosari, Sukamaju Region of North Luwu is significant. It is suggested that teachers should apply a scientific approach using a cooperative learning model using peer teaching methods to improve learning outcomes.